Subcutaneous cysticercosis due to Taenia crassiceps (Cestoda: Taeniidae) in an imported steppe lemming in Japan. (April 2022) - Chou, Shyun; Ozawa, Masato; Matsubara, Katsuki; Tamukai, Kenichi; Tokiwa, Toshihiro
Abstract: This study describes a subcutaneous proliferative cysticercosis in a pet steppe lemming, Lagurus lagurus (Rodentia: Cricetidae), bred and imported from Czech Republic into Japan. Numerous metacestodes were collected from the subcutaneous cystic lesion of the left medial thigh. Four surgical removals were coupled with anthelmintic treatment but ended with recurrence. Based on morphological features and mitochondrial DNA sequences, the metacestodes were identified as the larval stage of Taenia crassiceps (Zeder, 1800). This is the first case of infection with larval T. crassiceps in rodents of the genus Lagurus, and becomes the third case of the parasite detected from imported animals in Japan. Related public health concerns are discussed. Highlights: First case of subcutaneous cysticercosis in imported steppe lemming Cestode larvae were in the subcutaneous mass in the left medial thigh. These larvae were identified as Taenia crassiceps. Lagurus recognized as a new intermediate host for this parasite.